The Illusion of Precision and the Role of the Renminbi in Regional Interaction - Cheung, Yin-Wong; Chinn, Menzie D., Eiji Fujii (My University, 2006)
The Chinese renminbi might not be as undervalued as many analysts claim. They find that the currency might even be slightly overvalued, although they concede that this is a small possibility. Changes in China's currency value should be approached very carefully, as abrupt policy changes may cause unintended damage to China's difficult-to-manage economy.